Penang medical centre system (PMCS) / Mala Arumugam - Mala, Arumugam (2003)
Penang Medical Centre System (PMCS) is a web-based registration system aimed to help hospital/clinic to achieve a balance between providing the best possible care for patient and minimizing risk to organize all the procedures at the same time. Users have the possibility to access information from the database from any location at any time as long as they connect to the Internet. The target users of this PMCS system are normally the Physician, Nurse/Staff and Pharmacist. PMCS mainly focuses on the Registration, which is part of the Health Information System. PMCS is divided into four modules: the Registration module, the Scheduling module, the Patient History module and Admission and Discharge module. A combination of waterfall model and prototyping approach was selected for the development process because it supports the rapid application development and reduces the risk involved. Besides that, Active Server Pages are also selected to develop this application on the Windows XP Professional; moreover they integrated well with Microsoft Access 2000 for database application. Extensive research and background surveys on all topics involved have been conducted to determine the feasibility of the system and what is required from this proposal. This survey is done to ensure a higher level of accuracy in the designing process, along with a better knowledge base to begin with when the actual system development begins. All these activities are aimed at achieving the best outcome; which is to create a comprehensive Health Information System to cater the needs and requirement of the users.